Penyebab Resiko Bunuh Diri Di Masa Pandemi Covid-19 - Renta Sianturi; Delia Nurmalita; Elisa Puspitasari; Ridha Annisa Wicaksana; Ameliya Sarwani Putri; Ajeng Ayu Kutianti; Sitti Noer Shabrrina (Viva Medika, 2023)
During the Covid-19 pandemic, many people experienced positive effect around society, economic and mental impacts. For example Termination of Employment, Stress due to independent isolation which can lead to discrimination. Suicide has three categories namely gesture, threat, and attempt. The method of writing articles is carried out by Literature Review using 10 articles with the Google Scholar Database, Science Direct, Pubmed, NCBI which are limited by the year of publication from 2019-2022. Based on 10 articles, it was found that the impact of the risk of suicide, namely female sex was the most common, there was bullying in introverted individuals, anxiety about contracting Covid-19, worry about being laid off from work, and worry about safety for the family. Therefore the role of the family is very important for individuals